ASSESSMENT OF BIOLOGICAL ACTIVITY AND ELEMENT ANALYSIS OF PSYLLIOSTACHYS SPICATA (W ILLD.) NE VSKI - M.Fidan (Journal of Animal and Plant Sciences, 2018)
This study was conducted to determinethe antioxidant activity, total phenolic and flavonoid contents and also detection of phenolic compounds and element composition of Psylliostachys spicata by extraction of two different solvents (ethanol 80% andpure water) .18 different phenolic compounds and 19 elements were determined from the P. spicata which collected from the Akdomu_ salt area of Siirt province (Turkey).Total phenolic content was determined as 30.65 -1 -1 mg mL and 6.39 mg mL in ethanol and water extracts, respectively. The total flavonoid content was found as73.29 mg -1 -1 mL and 19.89mg mL in ethanol and water extract. The antioxidant activity wasdetermined by DPPH assay. The -1 inhibition rates in 1mg mL concentration in ethanol and water extracts were determined as 93.91% and 41.73%, -1 -1 respectively. The obtained IC50 value was 0.058 mg mL for ethanol and 1.196 mg mL for water extract. The FRAP -1 -1 -1 assay of P. spicata was determined as 774.440 mM mL mM mL in the ethanol and 74.074 mM mL in the water extract. According to the results of element analysis,P. spicata has high antioxidant capacity and potential to be used as an accumulator plant for halophytic areas in the future. That is why combating microorganisms using plants is
Keywords: Total phenolic-flavonoid; phenolic compound; element analysis; Psylliostachys spicata; Turkey.